ANALISIS PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP KINERJA - Ahmad Murad (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
The objective of this study aims is to analyze the influence of the initial review of competence and independence of the internal watchdog unit As well as the implementation of Good Corporate Governance Against the boarding costs Rural Banks (BPR) on the island of Lombok. Part of the problem is big Facing due Posted Posted Company Human resources The management is not true. Population Research Is Rural Banks (BPR) on the island of Lombok West Nusa Tenggara Barat (NTB) which covers an area of West Lombok district Central Lombok, East Lombok and North Lombok with using the survey method. Data retrieval is done with census method were 42 rural banks (BPR). Data obtained as much as 35 questionnaires spread questionnaires to All The Rural Bank There is on the island of Lombok, The analysis tool used is multiple linear regression. Research shows that the initials, Transparency. accountability, responsibility, independence and fairness influence on Against Corporate boarding costs. By simultaneous Competence, Independence And Good Corporate Governance influence Bank Where can take objective decisions free of any pressure from any party. Then the bank can not avoid the dominance of The Fair Posted stakeholders affected Posted NOT any unilateral interests and free from conflict of interest (conflict of interest). Of the five variables Tbk got a strong fence influence is a variable Justice, so that showed in the company are honesty hearts Management Company and Bank Always pay attention on stakeholders need based on the principle of harmony and fairness